2017
DOI: 10.14366/usg.15055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors influencing arterial Doppler waveforms in an in vitro flow phantom

Abstract: PurposeThe aim of this study was to investigate factors that influence arterial Doppler waveforms in an in vitro phantom to provide a more accurate and comprehensive explanation of the Doppler signal.MethodsA flow model was created using a pulsatile artificial heart, rubber or polyethylene tubes, a water tank, and a glass tube. Spectral Doppler tracings were obtained in multiple combinations of compliance, resistance, and pulse rate. Peak systolic velocity, minimum diastolic velocity, resistive index (RI), pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…In addition, determining the severity of PAD in patients with CLI can be challenging as a result of the presence of noncompressible arteries. 12 Sung et al 32 showed no consistent tendency of the influence of the compliance on the changes in peak systolic velocity, AT, or acceleration index, thus suggesting there is also no influence in ACC max when the compliance changes, as in a calcified vessel. Therefore, we conclude that ACC max can be clinically superior to other noninvasive measurements, particularly in patients with diabetes and/or CLI, as ACC max is measured distal to the stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, determining the severity of PAD in patients with CLI can be challenging as a result of the presence of noncompressible arteries. 12 Sung et al 32 showed no consistent tendency of the influence of the compliance on the changes in peak systolic velocity, AT, or acceleration index, thus suggesting there is also no influence in ACC max when the compliance changes, as in a calcified vessel. Therefore, we conclude that ACC max can be clinically superior to other noninvasive measurements, particularly in patients with diabetes and/or CLI, as ACC max is measured distal to the stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the study recruited selected population with many exclusion criteria to avoid confounding variables; thus, the results cannot be applied to general ADHF population. Renal AT depends on heart rate, 22,23 and because renal AT was not adjusted to the heart rate in our study, our results should be applied with caution in patients with heart rate outside the range (70–115 beats per minute) of heart rate in our population.…”
Section: Renal Resistivity Index and Worsening Of Renal Functionmentioning
confidence: 79%
“…Intrarenal variables include maximal velocity of blood flow, arterial compliance, and vascular resistance 22,23 while cardiovascular variables include systolic and diastolic pressure and time, pulse pressure, cardiac output, and heart rate. 22,23 Accordingly, AT in ADHF is a moving target that reflects the dynamic interactions of the aforementioned variables. This was obvious in our study where renal AT showed significant shortening in the first 24 h when compared with admission values; on the other hand, renal AT was longer in patients with WRF compared with patients without.…”
Section: Discussionmentioning
confidence: 99%
“…Sung et al [13] studied factors affecting the pulsed Doppler waveform using a closed-circuit in vitro blood flow model. They reported that in cases, where the vascular compliance at the distal and the proximal locations of pulsed Doppler waveform measurement was low, it rapidly reached a peak in the initial systolic period, and also presented a mild bimodal peak pattern.…”
Section: Discussionmentioning
confidence: 99%